2022
DOI: 10.3389/fcvm.2022.987008
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical circulatory support in ventricular arrhythmias

Abstract: In atrial and ventricular tachyarrhythmias, reduced time for ventricular filling and loss of atrial contribution lead to a significant reduction in cardiac output, resulting in cardiogenic shock. This may also occur during catheter ablation in 11% of overall procedures and is associated with increased mortality. Managing cardiogenic shock and (supra) ventricular arrhythmias is particularly challenging. Inotropic support may exacerbate tachyarrhythmias or accelerate heart rate; antiarrhythmic drugs often come w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…A number of studies have shown benefit in supporting patients at high risk for hemodynamic decompensation with MCS during VT ablation. 1 , 6 , 7 , 11 , 12 The Impella CP is frequently used given ease of placement from the femoral artery and up to 4.3 L/min of support. Other options for percutaneous support include the TandemHeart (Cardiac Assist, Inc, Pittsburg, PA), which is inserted through a 21F venous cannula placed transseptally in the left atrium with 17F arterial return cannula as well as VA ECMO.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of studies have shown benefit in supporting patients at high risk for hemodynamic decompensation with MCS during VT ablation. 1 , 6 , 7 , 11 , 12 The Impella CP is frequently used given ease of placement from the femoral artery and up to 4.3 L/min of support. Other options for percutaneous support include the TandemHeart (Cardiac Assist, Inc, Pittsburg, PA), which is inserted through a 21F venous cannula placed transseptally in the left atrium with 17F arterial return cannula as well as VA ECMO.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Although VA ECMO can provide complete circulatory support, it has a higher risk of vascular complications, it can increase LV afterload, thereby worsening LV function, and is resource intensive. 1 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations